2020
DOI: 10.1007/s10592-020-01305-2
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity of the glass sponge Vazella pourtalesii in response to anthropogenic activities

Abstract: Establishment of adequate conservation areas represents a challenging but crucial task in the conservation of genetic diversity and biological variability. Anthropogenic pressures on marine ecosystems and organisms are steadily increasing. Whether and to what extent these pressures influence marine genetic biodiversity is only starting to be revealed. Using 16S rRNA gene amplicon sequencing, we analysed the microbial community structure of 33 individuals of the habitat-forming glass sponge Vazella pourtalesii,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…If this is so, it means that the functional integration between the sponge and the microbes involved in the ammonium routes is more delicate and habitat-dependent than that involved in the phosphate metabolism. In line with this view, a recent study revealed significant differences in the microbiota between individuals of V. pourtalesii grown on natural substrata and individuals grown on adjacent artificial substrata that raised a mere couple of meters from the sea bottom (Busch et al, 2021). The individuals growing on the artificial substratum were significantly enriched in Bacteroidetes, Verrucomicrobia and Cyanobacteria compared to those growing on natural substrata.…”
Section: Net Flux Of Nutrients and Ecological Implicationsmentioning
confidence: 72%
See 1 more Smart Citation
“…If this is so, it means that the functional integration between the sponge and the microbes involved in the ammonium routes is more delicate and habitat-dependent than that involved in the phosphate metabolism. In line with this view, a recent study revealed significant differences in the microbiota between individuals of V. pourtalesii grown on natural substrata and individuals grown on adjacent artificial substrata that raised a mere couple of meters from the sea bottom (Busch et al, 2021). The individuals growing on the artificial substratum were significantly enriched in Bacteroidetes, Verrucomicrobia and Cyanobacteria compared to those growing on natural substrata.…”
Section: Net Flux Of Nutrients and Ecological Implicationsmentioning
confidence: 72%
“…In order to examine the microbial diversity in the studied sponges, 13 individuals of V. pourtalesii were collected from Sambro Bank and 13 of S. rosea from Schulz Bank. The sample processing procedure is described in detail elsewhere (Busch et al, 2020(Busch et al, , 2021; see also these references for data availability). Briefly, from each sponge individual chunks of tissue were subsampled, rinsed and frozen at −80 • C until DNA extraction.…”
Section: Diversity and Functional Gene Analysis Of Associated Microbiotamentioning
confidence: 99%
“…Members of the genera Hertwigia and Pheronema were absent from the Steinert study. Using the amplicon sequence variant (ASV) technique of classification [ 42 ], a greater dissimilarity in alpha-diversity was also observed between 33 replicates of the hexactinellid Vazella pourtalesii , compared to the microbiome of surrounding seawater and sediment, at ASV and phylum level [ 24 ]. It is therefore relevant to consider the differences in community composition between biological replicates of the same host species, particularly for those that have not been previously investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Vertical distribution has important consequences for larval transport and dispersal trajectories (Edwards et al, 2007;Gary et al, 2020;Wang et al, 2020). However, the vertical movements of V. pourtalesii larvae, like those of many sponge species, remain unknown (Kenchington et al, 2019), although settlement of V. pourtalesii has been observed on artificial substrates about 5 m off the bottom (Busch et al, 2020). In the absence of better information, larval release was modeled at three depths: the average seabed depth of recorded occurrences of V. pourtalesii in the relevant regional group (Table 1), mid-water from the seabed to the surface, and the surface, to capture three vertical strata that might be reached through active swimming behavior (Vaz et al, 2016).…”
Section: Biological Traits Of V Pourtalesii For Particle Tracking Modelingmentioning
confidence: 99%